2015
DOI: 10.1590/s1517-838246220130541
|View full text |Cite|
|
Sign up to set email alerts
|

Descriptive study of onychomycosis in a hospital in São Paulo

Abstract: Onychomychosis, a nail fungus infection is the most frequent nail ailment, constituting about half of all nail disorders. It can be caused by dermatophytes, non-dermatophytes, yeasts and Prothoteca spp. Methods include 5407 samples of patients with suspected onychomycosis, studied from January 2002 to December 2006, by direct mycological examination and fungi culture. The diagnosis of onychomycosis was confirmed in samples from 3822 direct mycological and/or culture positive. The diagnosis was established by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
12
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
8
12
1
2
Order By: Relevance
“…Dermaphytoses were the most common mycoses in the analysed population, with tinea capitis and tinea unguium (toenails) predominating. Tinea capitis has been described in different countries as the most common fungal infection in school‐aged children, and in our study similar findings were found. With respect to aetiology, M. canis was cultured in 89.7% of cases, the source of infection might have been infected animals, healthy asymptomatic carriers, or fomites .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Dermaphytoses were the most common mycoses in the analysed population, with tinea capitis and tinea unguium (toenails) predominating. Tinea capitis has been described in different countries as the most common fungal infection in school‐aged children, and in our study similar findings were found. With respect to aetiology, M. canis was cultured in 89.7% of cases, the source of infection might have been infected animals, healthy asymptomatic carriers, or fomites .…”
Section: Discussionsupporting
confidence: 91%
“…The frequency and distribution of this group of fungi can vary according to the geographical location, socioeconomic, cultural and migratory factors . In Latin America, Microsporum canis and Trichophyton rubrum are the most frequently reported aetiological agents of tinea capitis and tinea unguium respectively . In adult population, moulds are increasingly involved in skin and nail infections worldwide, unfortunately epidemiological descriptions of these dermatomycosis among children are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Onychomycosis is a stubborn, difficult to treat, fungal infection of the nail bed and plate, and accounts for approximately 50% of all nail disease . Studies estimating the prevalence of onychomycosis have recently been published from Italy, Iran and Brazil . The prevalence of onychomycosis in the North American population has been reported to be as high as 13.8% .…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies estimating the prevalence of onychomycosis have recently been published from Italy, 2 Iran 3 and Brazil. 4 The prevalence of onychomycosis in the North American population has been reported to be as high as 13.8%. 5 Studies differ in terms of the selected sample (population-or hospitalbased) and geographic location 6 and these factors may account for the variation in prevalence estimates reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…laurentii ) were isolated of onychomycosis in type 2 diabetes mellitus patients [5] . Also, Prothoteca spp was reported as the first causative agent of onychomycosis in Brazil which was the 3rd case in the world [16] . The distribution of pathogens of onychomycosis is not uniform.…”
Section: Discussionmentioning
confidence: 99%